A polysaccharide from Eclipta prostrata alleviates experimental autoimmune encephalomyelitis through inhibiting Th17 cells. (1st December 2018) - Li, Ning; Shi, Songshan; Yang, Feifei; Wang, Hongwei; Su, Juan; Huang, Fei; Wu, Hui; Wu, Xiaojun; Wang, Shunchun
Highlights: EAP20-1 is a polysaccharide isolated and purified from Eclipta prostrata . EAP20-1 inhibited lymphocytes proliferation dose-dependent in vitro . EAP20-1 could alleviate the severity of experimental autoimmune encephalomyelitis mice. This alleviative effect was related to its inhibition on Th17 cells differentiation. Abstract: Eclipta prostrata has long been used as a medicinal herb in China. EAP20-1, a homogeneous polysaccharide with anti-complementary activity had been obtained from E. prostrate by using anion-exchange and size-exclusion chromatography. In this study, we found that EAP20-1 could inhibit in vitro lymphocyte proliferation stimulated by concanavalin–A or anti-CD3/anti-CD28 antibodies. Furthermore, in experimental autoimmune encephalomyelitis (EAE) mice, EAP20-1 treatment relieved the clinical symptoms, accompanied by reduced neuroinflammation and demyelination in spinal cords. Mechanistically, EAP20-1 reduced the mRNA expression of interleukin (IL)-17, IL-22, and RAR-related orphan receptor gamma t (RORγt) in the spleen; inhibited auto-reactive T cell proliferation and decreased the percentage of Th17 cells in response to myelin oligodendrocyte glycoprotein (MOG35-55 ) ex vivo . Moreover, EAP20-1 directly inhibited naïve CD4 + T cells differentiate into Th17 cells in vitro . These results indicating EAP20-1 could benefit EAE through inhibiting Th17 cell differentiation and suggesting a therapeutic potential of EAP20-1 in MS.